Ignimbrite Analyses of Batur Caldera, Bali, based on 14C Dating - Sutawidjaja, Igan S. (Geological Agency, 2009)
http://dx.doi.org/10.17014/ijog.vol4no3.20094The Batur Caldera, in the northeastern part of Bali Island, is an elliptical collapse structure 13.8 by 10 km in size and another circular composite collapse structure with a diameter of 7.5 km in its centre. Two stages of the collapse were interrupted by silicic andesite lavas and domes. The first collapse was initiated by the eruption of about 84 km3 of the dacitic